Enhancing the Oral Bioavailability of Candesartan Cilexetil Loaded Nanostructured Lipid Carriers: In Vitro Characterization and Absorption in Rats after Oral Administration - Walid Anwar; Hamdy M. Dawaba; Mohsen I. Afouna; Ahmed M. Samy; Mohammed H. Rashed; Abdelaziz E. Abdelaziz (MDPI AG, 2020)
Candesartan Cilexetil (CC) is a prodrug widely used in the treatment of hypertension and heart failure, but it has some limitations, such as very poor aqueous solubility, high affinity to P-glycoprotein efflux mechanism, and hepatic first-pass metabolism. Therefore, it has very low oral bioavailability. In this study, glyceryl monostearate (GMS) and Capryol™ 90 were selected as solid and liquid lipids, respectively, to develop CC-NLC (nanostructured lipid carrier). CC was successfully encapsulated into NLP (CC-NLC) to enhance its oral bioavailability. CC-NLC was formulated using a hot homogenization-ultrasonication technique, and the physicochemical properties were characterized. The developed CC-NLC formulation was showed in nanometric size (121.6 ± 6.2 nm) with high encapsulation efficiency (96.23 ± 3.14%). Furthermore, it appeared almost spherical in morphology under a transmission electron microscope. The surgical experiment of the designed CC-NLC for absorption from the gastrointestinal tract revealed that CC-NLC absorption in the stomach was only 15.26% of that in the intestine. Otherwise, cellular uptake study exhibit that CC-NLCs should be internalized through the enterocytes after that transported through the systemic circulation. The pharmacokinetic results indicated that the oral bioavailability of CC was remarkably improved above 2-fold after encapsulation into nanostructured lipid carriers. These results ensured that nanostructured lipid carriers have a highly beneficial effect on improving the oral bioavailability of poorly water-soluble drugs, such as CC.